FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KADAR KOLESTEROL HDL (Analisis Data of The Indonesian Family Life Survey 2007/2008) - ., Mamat; ., Sudikno (PERSATUAN AHLI GIZI INDONESIA, 2010)
DETERMINANT OF HDL CHOLESTEROL LEVEL (Indonesian Family Life Survey DATA ANALYSIS 2007/2008)Low level HDL cholesterol could lead to variety of diseases such as Coronary Heart Disease (CHD), hypertension and stroke. Several causes of the low level HDL cholesterol are smoking habit, less physi cal activity, obesity, and fiber consumption. This study aimed to identify factors associated with HDL cholesterol using Indonesian Family Life Survey (IFLS) data 2007/2008. The study design was cross sectional. The population was Indonesian family and for sample determination, multi-stage sampling were done using Probability Proportional to Size (PPS) and the final sampling was done using Simple Random Sampling (SRS). Data were collected based on existing secondary data report on the IFLS in the year 2007/2008. Data analysis used complex sampling design with logistic regression analysis aiming to see the variables associated with HDL cholesterol level. Results showed that respondents having abnormal HDL cholesterol were 76.9 percent. There was a relation among smoking habit, sex, obesity, activity and fiber consumption, and HDL cholesterol (p< 0.05). The results also showed that sex was the most dominant variable related to HDL cholesterol level with odd ratio 2,64 (95 % CI: 2,255 – 3,092) – 1,348). It can be concluded that there was high level abnormal cholesterol on people who had smoking habit, less physical activity and less fiber consumption, male, and obese.Keywords: HDL, cholesterol level, IFLS 2007/2008